Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content: 1. Awareness and practices of king Khalid university students in virtual clothing Dr. Amani Shaaban Ali Mohamed 2. The feasibility of the Palestinian movement to implement boycott systems for a state of Zionist occupation: a reading of the results, challenges, and the future of the movement Mr. Mohammad A. Jaradat 3. The role of national platforms in charitable work (Ehsan platform as a model) Society of the Kingdom of Saudi Arabia Mrs. Bashaier Abdullah Al-Zahrani 4. An Analysis of Visual Metaphor to Understand Creativity in Contemporary Art Dr. Rihab Abdullah Alghathami 5. Mechanisms of digital technology in establishing the quality of scientific research Mrs. Lallouche Samira 6. The Implications of Covid-19 on Increased Social Distancing for At-Risk Youth in Israel’s Arab Community Dr. Rodayna Kamal Badir, Dr. Anan Abu-Saleh , Dr. Omar Abd -Alrahim Nasrallah 7. The Constructive Contexts of the Artistic Profile of Nations and populations Dr. Fouzia Bouchareb